PENGARUH ABDOMINAL STRETCHING EXERCISE TERHADAP PENURUNAN INTENSITAS NYERI HAID (DISMINORE) PADA REMAJA PUTRI DI SMP N 27 KOTA BATAM - Endah Kirana Harahap; Desi Ernita Amru, Renny Adelia Tarigan (Jurnal Kesehatan, 2024)
Dysmenorrhea is a gynecological disorder caused by an imbalance in the hormone progesterone which will result in pain experienced by women. Abdominal Stretching Exercise can increase the release of endorphins so that the pain threshold decreases. The aim of this study was to determine the effect of Abdominal Stretching Exercise on reducing the intensity of menstrual pain (dysmenorrhea) in adolescent girls. This type of preexperimental research uses one group pretest-post test design. The sample in this study was 15 female students at SMPN 27 Batam City who experienced dysmenorrhea, who were taken using a purposive sampling technique. The data analysis technique uses the paired sample T-Test. The results of the study showed that the mean value of dysmenorrhea pain level for young women before being given Abdominal Streching Exercise was (2.80), then there was a decrease in the mean after being given Abdominal Streching Exercise to (2.00). The statistical test results have a p-value = 0.00 (<0.05), meaning there is a significant influence between the level of dysmenorrhea before and after being given the Abdominal Streching Exercise intervention to young women at SMPN 27 Batam City. The conclusion of this study is that there is a significant influence between the level of dysmenorrhea before and after being given the Abdominal Streching Exercise intervention to young women at SMPN 27 Batam City. It is hoped that young women will do effelurage massage themselves or with the help of other people as a non-pharmacological therapy to reduce and prevent dysmenorrhea.